DIAGNOSIS AND SURGICAL TREATMENT TACTICS OF COMPLICATED FORMS OF MECKEL'S DIVERTICULUM IN CHILDREN (International journal of artificial intelligence, 2025)
Meckel's diverticulum is one of the most common congenital anomalies of the gastrointestinal tract, found in about 2-3% of the general population. Although it is often asymptomatic, complications can arise, particularly in pediatric patients. This article explores the diagnosis and surgical treatment strategies for complicated forms of Meckel's diverticulum in children. The complications, such as bleeding, intestinal obstruction, and inflammation, necessitate prompt and accurate diagnosis through imaging techniques like ultrasound, CT scans, and technetium-99m scintigraphy. The article discusses the various surgical approaches, including resection of the diverticulum, and highlights the importance of early intervention to avoid severe consequences. The goal of this review is to present modern diagnostic tools and surgical tactics that can lead to improved outcomes in pediatric patients.